Multifocal angiomyolipoma involving kidney and regional lymph nodes in patient with tuberous sclerosis complex- A Rare case with review of literature - Mylarappa, Prasad; Patil, Avinash B; Puvvada, Sandeep; Pathade, Amey; Ramesh, D (Asian Journal of Medical Sciences, 2015)
Tuberous sclerosis complex is rare neurocutaneous syndrome involving central nervous system and lesions in skin. Tuberous sclerosis with multifocal angiomyolipoma involving kidney and lymph nodes is even rarer. Asian Journal of Medical Sciences Vol.7(2) 2015 96-99